2021
DOI: 10.1021/acsnano.0c08718
|View full text |Cite
|
Sign up to set email alerts
|

Tunable High Speed Atomic Rotor in Bi2Se3 Revealed by Current Noise

Abstract: The ability to manipulate individual atoms and molecules using a scanning tunneling microscope (STM) has been crucial for the development of a vast array of atomic-scale devices and structures ranging from nanoscale motors and switches to quantum corrals. Molecular motors in particular have attracted considerable attention in view of their potential for assembly into complex nanoscale machines. Whereas the manipulated atoms or molecules are usually on top of a substrate, motors embedded in a lattice can be ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Very recently, Desvignes et al reported a diatomic rotor in Fe doped Bi 2 Se 3 where the atomically sized Fe defect is embedded in the crystal structure. 28 Here we report, for the first time, the construction of a Cr− Cs/Fe−Cs diatomic rotor in a newly discovered kagome superconductor CsV 3 Sb 5 , 29,30 which has been reported to exhibit rich surface effects such as symmetry breaking orders, 31−36 carrier doping, 37,38 and polarity. 39 switching rates suggests the effects of symmetry breaking charge orders on the rotors.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Very recently, Desvignes et al reported a diatomic rotor in Fe doped Bi 2 Se 3 where the atomically sized Fe defect is embedded in the crystal structure. 28 Here we report, for the first time, the construction of a Cr− Cs/Fe−Cs diatomic rotor in a newly discovered kagome superconductor CsV 3 Sb 5 , 29,30 which has been reported to exhibit rich surface effects such as symmetry breaking orders, 31−36 carrier doping, 37,38 and polarity. 39 switching rates suggests the effects of symmetry breaking charge orders on the rotors.…”
mentioning
confidence: 97%
“…Such a strategy also inspires the search for a diatomic rotor. Very recently, Desvignes et al reported a diatomic rotor in Fe doped Bi 2 Se 3 where the atomically sized Fe defect is embedded in the crystal structure …”
mentioning
confidence: 99%
“…The tetradymites have layered crystal structures (Figure a). We should care about the unintended intergrowth of magnetic impurities of Fe–Se compounds promoted by Fe doping. This intergrowth may occur over a certain temperature range and be easily driven by an inhomogeneous Fe distribution. Indeed, owing to special care such as homogeneous mixing at high temperatures and rapid quenching, we grew Fe-doped Bi 2 Te 2 Se and Fe-doped BiSbTe 2 Se (Fe-BSTS) as high bulk-insulating magnetically doped TIs , and reported observation of unusual proximity effects .…”
mentioning
confidence: 99%